Predictors for lower urinary tract symptoms in patients underwent radical prostatectomy: implications for postoperative nursing care. Issue 9 (12th September 2021) - Yilin, Zeng; Fenglian, Jiang; Yuanling, Wu; Chunye, Guo; Shuang, Liu; Peizhen, Liu
Abstract: Aims and Objectives: The aim of this study was to evaluate the risk factors for lower urinary tract symptoms in prostate cancer patients underwent radical prostatectomy, thus providing therapeutic evidence for post‐operative nursing. Background: Prostate cancer is one of the most commonly diagnosed male malignancy in recent years. With surgical treatments, patients with prostate cancer indeed have satisfying survival rate. However, the presence of postprostatectomy lower urinary tract symptoms which affect quality of life significantly is more worthy of attention. Design: Patients underwent surgical therapies were followed up and the symptoms were recorded. Methods: A total of 65 prostate cancer patients underwent radical prostatectomy from January 2019 to October 2020, and pathologically diagnosed with prostate cancer were enrolled in our study. These patients were followed up 3 months after surgery and their medical records were retrospectively collected and analysed. Results were reported according to the STROBE Statement. Results: The incidence of post‐operative lower urinary tract symptoms at 3 months after surgery is similar to that of pre‐operation. Univariate and multivariate analyses revealed that the independent risk factor for postprostatectomy lower urinary tract symptoms is body mass index, whereas pelvic floor muscle exercise is a protective factor. Conclusions: The incidence of postprostatectomy lower urinary tract symptoms is non‐negligible, which significantly affects quality of life. Body mass index is found as an independent risk factor for postprostatectomy lower urinary tract symptoms, while pelvic floor muscle exercise is a strong protector. Relevance to clinical practice: Patients with prostate cancer would benefit from post‐operative pelvic floor muscle exercise. These findings contribute to tailor post‐operative nursing strategy.